A review of Panurgus (Pachycephalopanurgus), with the description of a new species from Spain - Patiny, Sébastien; Ortiz-Sánchez, F. Javier; Michez, Denis (Zootaxa, 2005)
Study of recently collected bees from south-eastern Spain revealed a new species of subgenus Panurgus (Pachycephalopanurgus) Patiny, 1999, closely related to P. canescens Latreille, 1811, and P. calceatus Pérez, 1895. Within this group of three species, P. meridionalis sp.nov. is characterized by the presence of a pair of latero-ventral teeth on the third tergum of the male (unique among Panurginae). This new species is only the second species of Pachycephalopanurgus recorded from Europe, the other five being North African. Distributional patterns in subgenus Pachycephalopanurgus are mapped and summarized.